Foods and poetry - Μύσνικ, Ζοζέ (The Greek Review of Social Research, 2010)
The knowledge of foods as any type of knowledge requires different approaches. The study of poetic texts of various civilizations constitutes a priceless field for the knowledge of food. In this paper we begin to look for the connections of poetical experiences and poetic texts with the knowledge of foods. In second place we analyze the poetic language and its analogies with the gastronomic language. We will see then how this knowledge contributes to appreciate food cultures, clarifying the social links weaved around food, meals, festivities. What the individuals eat, by reveals they belong to a specific culture. In the third place we will analyze the role of the symbolic value of food, because the place of the individuals in a society is represented by symbols in which these individuals recognize them. And these symbolic values conditions eating habits strongly, and even the market prices of food.